Perturbation theory for Wannier resonance states affected by ac field - Glück, M.; Kolovsky, A.R.; Korsch, H.J. (Physics letters. A, 1999)
The paper studies the effect of a weak ac field on the Wannier states, which are known to be the metastable states of a quantum particle in a periodic potential subject to a static field. Provided that the photon energy exactly matches the spacing of the Wannier–Stark ladder the system complex quasienergy spectrum is obtained. It is shown, in particular, that a weak ac field can increase the lifetime of the Wannier states by several orders of magnitude. The analytical results of a perturbation theoretical analysis are compared against the exact numerical calculation of the system spectrum.